DEVELOPMENT OF STUDENTS’ COMPETENCES DURING THE PEDAGOGICAL PRACTICE - Valentina I. Teslenko; Sergey V. Latyntsev; Nadezhda V. Prokopyeva (Высшее образование в России, 2016)
The article is devoted to the problem of increasing the efficiency of student teaching when training future teachers in the conditions of realization of a competence-based paradigm of education. The authors have offered an approach to the organization of students’ teaching in the modern educational environment of pedagogical higher education institution on the basis of the developed structural and substantial innovative model of competence-based development of a future teacher. The interconnected stages of carrying out student teaching are educed. Special technological cards characterizing different kinds of students’ activity were elaborated for effective management of competence-based development of a future teacher. The assessment of the level of formation of students’ professional competences was carried out on the basis of the estimated and diagnostic cards developed according to specified criteria. The experiment made by authors allowed to confirm the efficiency of the developed innovative model of students’ teaching practice.